Neale - Australia. Division of National Mapping ([Canberra] : NATMAP, 1987)
Topographic map with relief shown by contours, spot heights, form lines and hill shading.
Index to adjoining sheets.
Keywords: Neale Junction (W.A.) -- Maps; Topographic maps